2020
DOI: 10.3390/ijms21031036
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Hyaluronan Induces an Inflammatory Response in Ovarian Stromal Cells and Impairs Gamete Development In Vitro

Abstract: The ovarian stroma, the microenvironment in which female gametes grow and mature, becomes inflamed and fibrotic with age. Hyaluronan is a major component of the ovarian extracellular matrix (ECM), and in other aging tissues, accumulation of low molecular weight (LMW) hyaluronan fragments can drive inflammation. Thus, we hypothesized that LMW hyaluronan fragments contribute to female reproductive aging by stimulating an inflammatory response in the ovarian stroma and impairing gamete quality. To test this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 81 publications
3
33
0
Order By: Relevance
“…Decreased Has3 and increased Hyal1 expression in the ovarian stroma with age may be indicative of reduced synthesis coupled to increased fragmentation of HMW‐HA into LMW‐HA, contributing to ovarian HA loss with age. We previously demonstrated that LMW‐HA fragments can trigger a Th2 inflammatory response in ovarian stromal cells which is predicted to increase fibrogenic pathways (Rowley, et al, 2020). Thus, we evaluated HA mass distribution in individual ovaries from reproductively young and old mice using solid‐state nanopore sensor technology (Rivas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased Has3 and increased Hyal1 expression in the ovarian stroma with age may be indicative of reduced synthesis coupled to increased fragmentation of HMW‐HA into LMW‐HA, contributing to ovarian HA loss with age. We previously demonstrated that LMW‐HA fragments can trigger a Th2 inflammatory response in ovarian stromal cells which is predicted to increase fibrogenic pathways (Rowley, et al, 2020). Thus, we evaluated HA mass distribution in individual ovaries from reproductively young and old mice using solid‐state nanopore sensor technology (Rivas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…If dysregulated, ECM degradation may also trigger pathogen-free inflammation. For example, hyaluronan is a glycosaminoglycan that forms low molecular weight fragments during turnover, which have been shown in cultured murine stromal cells to increase the secretion of type 2 inflammatory cytokines and activate genes involved in eosinophil recruitment, while also leading to adverse effects on cultured follicles (Rowley et al 2020).…”
Section: Function: Signaling and Remodelingmentioning
confidence: 99%
“…In this publication, Urzua et al demonstrated an excessive accumulation of incompletely digested cell debris in the form of lipofuscin in reproductively aged mouse ovaries (Urzua et al, 2018 ). More recently, Rowley et al reported that age-related DAMPs, such as low molecular weight (LMW) hyaluronan fragments, may be a potential driver of the age-associated inflammation characteristic of ovaries from reproductively old mice (Rowley et al, 2020 ). However, whether accumulation of LMW hyaluronan fragments occurs in advanced reproductively aged ovaries is still under investigation.…”
Section: Introductionmentioning
confidence: 99%